ANALYSIS OF THE FACTORS AFFECTING STUDENTS’ INTEREST IN A CAREER IN SYARIAH BANKING - Kustina, Yeni; Hermawan Adinugraha, Hendri (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
The large number of graduates of the Sharia Banking Study Program who need to be more absorbed in the world of work according to their field of expertise is the core problem in this research. This research intends to analyze in depth the factors that influence students’ interest in pursuing a career in Sharia banking, a study on students of the Sharia Banking Study Program at UIN K.H. Abdurrahman Wahid Pekalongan. The method used in this research is a quantitative approach with an associative type. This research was conducted in the Sharia Banking Department, Faculty of Islamic Economics and Business, UIN K.H. Abdurrahman Wahid Pekalongan. This research will take place in 2023. The population of this research is active students of the Sharia Banking Department, UIN K.H. Abdurrahman Wahid, class of 2018-2020, with a total of 408 students. Sampling used a purposive sampling technique. The sample criteria selected were active students from Class 2018-2020, Department of Sharia Banking, UIN K.H. Abdurrahman Wahid Pekalongan, who have carried out Field Experience Practices at Sharia Financial Institutions totaling 80 students. The data collection technique uses a questionnaire. Data analysis methods use instrument tests (validity tests and reliability tests), classical assumption tests (data normality tests and multicollinearity tests), heteroscedasticity tests, multiple linear regression tests, and hypothesis tests (t-test (partial); f test (simultaneous); and determinant coefficient test (R2)). This research concludes that partial self-efficacy, financial appreciation, and social values ​​positively and significantly affect students’ interest in pursuing a career in Sharia banking. Job market considerations partially do not have a positive and significant effect on students’ interest in pursuing a career in sharia banking. Based on the results of the F test, it is stated that the variables of self-efficacy, financial rewards, and job market considerations simultaneously have a positive and significant effect on students’ interest in pursuing a career in Sharia banking.